KANDUNGAN LOGAM BERAT TEMBAGA (Cu) PADA SIPUT MERAH (Cerithidea sp) DI PERAIRAN LAUT DUMAI PROVINSI RIAU - Elya Febrita; Darmadi '; Thesa Trisnani (Biogenesis, 2011)
Conducted a study to determine the concentration of heavy metals copper ( Cu ) on the Red Snail ( Cerithidea sp ) on Sea waters Dumai conducted in May and June 2011. The method used was a survey method , in which the station is purposive determination of systematic sampling at three observation stations . The main parameters measured were cu metal content in sea water , sediments and Cerithidea sp and the level of accumulation of heavy metals Cu . While supporters of the parameters are temperature , brightness , salinity , pH , dissolved oxygen , organic matter content and the type of substrate . Heavy metal concentrations of Cu were analyzed using AAS ( Atomic Absorption Spectrophotometer ). The data were analyzed descriptions. The results showed Cu concentrations of heavy metals in sea water range from 0.102 ppm - 0.175 ppm. Cu content of heavy metals in sediments ranged from 1.323 ppm - 3.631 ppm. While the concentration of Cu on Cerithidea sp ranged from 1.264 ppm - 2.592 ppm. Cu concentration of heavy metals in marine waters Dumai has passed the threshold for sea water quality, while the heavy metal concentrations of Cu in Cerithidea sp has not passed the threshold. Biological value of Cu concentration factor on Cerithidea sp ranged from 12.3 to 19.3. This shows the level of accumulation of heavy metals Cu is low.Keywords: Cerithidea sp, Heavy Metal, Copper (Cu)